Post trabeculectomy situations: Hypotony - Priyanka Sudhakar; Meena G Menon (Kerala Journal of Ophthalmology, 2021)
Hypotony, characterized by a low intraocular pressure <6.5 mm Hg or <5 mm Hg with possible clinical complications, can lead to dreaded complications, posttrabeculectomy. It leads to a breakdown of blood-aqueous barrier, leading to an inflammatory cascade, scarring, and bleb failure, in the long term. It also predisposes to blebitis and other hypotony-related complications. Identifying the cause of hypotony, such as bleb leak or overfiltration, is vital to addressing the underlying cause. It can be managed conservatively with pressure patching, and medically with steroids or cycloplegics, or would require surgical bleb revision, depending on the cause and extend of underlying damage. In this article, we review the definition, pathophysiology, risk factors for hypotony, and posttrabeculectomy and identify the various possibilities, and their respective management strategies.